THE DYNAMICS OF PROSELYTIZING IN MAINTAINING RELIGIOUS HARMONY (Study of Da'i Methods in Da'wah in the city of Sibolga) - Harahap, Abdi Syahrial; Harahap, Muhammad Yunan (Proceeding International Conference of Science Technology and Social Humanities, 2022)
Islam is a religion of preaching. Preaching religion is a religion that aims to transmit and as a vehicle for spreading religion. Islam requires its adherents to be acquainted with the method and ability to spread religious teachings which in the Qur'an is called cinta makruf nahi munkar, which means inviting good and avoiding impoverishment. As proof whether these people understand whether they are with Islam or not, it will be seen when they are willing to do good and leave despicable acts. The ultimate goal of da'wah is to achieve human safety and happiness in this world and in the future. The city of Sibolga is a plural area that has a population of more than one ethnic group where each ethnic group has a different culture that they bring from their place of origin, hence interactions between different ethnic groups, especially the Toba Batak ethnic group and the Pesisir ethnic group. (Islam). Therefore, preachers and religious experts are needed who can maintain harmony between communities in the city of Sibolga.